2011
DOI: 10.2975/35.2.2011.111.116
|View full text |Cite
|
Sign up to set email alerts
|

Developing a quit smoking website that is usable by people with severe mental illnesses.

Abstract: The website usability recommendations provide some guidelines for interventionists developing web tools for people who experience serious psychiatric disabilities. In general, insights from the study highlight the need for thoughtful design and usability testing when creating a website for people with severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…We selected a behavioral rather than psychological measure of motivation because initiation of treatment is a stronger predictor of successful smoking cessation (Culhane et al, 2008) than assessments of intention or other psychological measures. Initiation of cessation treatment was assessed by blinded research staff at baseline and two-month follow-up with the Behavioral Motivation Index (Brunette, Ferron, McHugo, et al, 2011). This checklist assessed initiation of cessation medication and attendance at behavioral treatment for smoking cessation, as well as other clinician contact regarding smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected a behavioral rather than psychological measure of motivation because initiation of treatment is a stronger predictor of successful smoking cessation (Culhane et al, 2008) than assessments of intention or other psychological measures. Initiation of cessation treatment was assessed by blinded research staff at baseline and two-month follow-up with the Behavioral Motivation Index (Brunette, Ferron, McHugo, et al, 2011). This checklist assessed initiation of cessation medication and attendance at behavioral treatment for smoking cessation, as well as other clinician contact regarding smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
“…The web-based motivational decision support system was designed and tailored for smokers with severe mental illnesses (Brunette, Ferron, McHugo, et al, 2011). Similar to in-person interventions for this population, the system provides information and exercises that aim to increase awareness of the pros and cons of smoking, including its' health risks, via education, assessment, and feedback.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good and Sambhanthan [11] reported several website elements that people with depression and anxiety identified as being accessibility issues: distracting design, confusing menu options, poor navigation, time limited response forms, information overload, non-perceivable icons, slow response in websites loading information, poor organisation and presentation complicated language, poor content filters, excessive advertisements, and complex purchasing processes. Ferron et al [12] and Rotondi et al [10] concluded that people with severe mental disorders require sites that explicitly state instructions for their use, feature a shallow hierarchy of pages, use clear and explicit labels, large navigational cues and pop-up menus to reduce clicking. Findings from Rotondi et al [10] also reveal that these Web accessibility needs are distinct and are not covered by existing guidance and or Web-interface models.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough keyword search of several databases (i.e., MEDLINE, PsycARTICLES, CINAHL, Library, Information Science and Technology Abstracts, Computers and Applied Sciences Complete, ACM Digital Library, SpringerLink, OpenGrey) for Web accessibility, mental disorders and related terms only returned 3 directly relevant results (i.e., [10][11][12] as discussed earlier).…”
Section: Introductionmentioning
confidence: 99%